TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK BAGI HASIL PERTANIAN (MUKHABARAH) DI DESA KEBONDALEM KECAMATAN MOJOSARI KABUPATEN MOJOKERTO - Amanto, Sudrajat; Yasin, Ach (Universitas Negeri Surabaya, 2022)
Cooperation with a profit-sharing system is considered more profitable than a rental system, both for landowners and farmers. The people of the Mojosari sub-district did not clearly say that the contract they were carrying out was mukhabarah. The purpose of this study was to find out the practice of sharing agricultural products (mukhabarah), a review of Islamic law and the reasons why the villagers of Kebondalem cooperate for agricultural products (mukhabarah). This type of research is qualitative. The subject of this research is the owner of the field and the farmer/farm laborer or cultivator. Based on these criteria, five research subjects were found. Informant retrieval technique using purposive sampling technique. Data collection techniques used are observation, interviews and documentation. Data analysis in this study refers to the interactive analysis model proposed by Huberman and Miles. The results showed that The practice of agricultural production sharing (mukhabarah) in Kebondalem Village with a production sharing agreement with the maro system (half) and the 30/70 system, namely 30% for land owners and 70% for small farmers. The review of Islamic Economics in the application of profit sharing which is carried out daily with the mukhabarah system in the village of Kebondalem, Mojosari District, Mojokerto Regency which has not been fully carried out based on existing Islamic rules, but they use it according to the habits of the local community, namely by not specifying the period of validity. mukhabarah contract and the distribution of the results in accordance with the agreement of the land owner with the tenant farmer only. The mukhabarah transaction process carried out in the village of Kebondalem can be categorized as a valid cooperation because it contains the principle of muamalah, namely the existence of an element of mutual willingness and is a custom that does not conflict with the Qur'an and Hadith and does not contain any harm. The aspect of justice that occurs in the practice of profit sharing in the village of Kebondalem is not very visible, because both parties are mutually pleased, understand each other and are considerate of each other.